Islam dalam Demokrasi Bangladesh - Ilyas, Muhammad Azizzullah (STAIN Curup, 2019)
Isl?mic teachings believed by some to be inseparable from the life of Isl?mic society, including in-state life which makes democracy a political method complete with party systems but issues heard in Bangladesh that also uses the political method of democracy in the state, parties that embrace Isl?mic ideology a difficult problem was even declared a band party. This study aims to see, analyze with a descriptive approach with library data sources to see the facts that occur, the role of Isl?mic parties and find patterns of an Isl?mic party in Bangladesh, especially the JIB party (Jamaat Islamiyah Bangladesh) in democracy. The results of the study found that Bangladesh, including Flawed Democracy and the Bangladeshi regime, made the reasons for terrorism and history a pretext to suppress the Isl?mic party which is also an opposition government party, especially JIB, which is a fusion of the Bangladesh Muslim League and Isl?mic Democratic League. But despite the party's forbidden right-wing but has alliances with other major parties such as the BNP and Awami League and JIB still articulates through the mouthpiece of secular parties, even the voice of Islamic parties remains the key to BNP victory in elections.